A study on effectiveness of pedestrian bridge utilization at Jalan Tanah Putih - Junaidi, Rahman (2017)
Transportation plays an important role in achieving sustainable development. The increasing dependency of private vehicles in Kuantan Town has been increasing the number of road accident especially for pedestrian during crossing road Jalan Tanah Putih. A functional pedestrian bridge will require for a smooth transfer of pedestrian crossing the road and decrease road accident for pedestrian. Therefore, a pedestrian bridge must be properly designed as to maximize the effectiveness of the bridge.